The Importance of Mesodinium rubrum at Post-Spring Bloom Nutrient and Phytoplankton Dynamics in the Vertically Stratified Baltic Sea - Lips, Inga; Lips, Urmas (Frontiers in Marine Science, 2017)
The inter-annual dynamics of the photosynthetic ciliate Mesodinium rubrum in the central Gulf of Finland in spring-summer continuum during five years were followed. The analysis was mainly based on high-resolution measurements and sampling in the surface layer along the ferry route Tallinn-Helsinki. The main purpose was to analyze the dynamics of M. rubrum biomass, its contribution to the photosynthetic plankton biomass, and the influence of water temperature and variations of inorganic nutrients in the surface and sub-surface layer on its dynamics. The analysis revealed that the outcome of the M. rubrum bloom in spring was largely related to the surface layer water temperature – in the years of earlier warming, the higher biomass of this species was formed. The photosynthetic ciliate was an important primary producer in all studied years during the late phase or post-spring bloom period in the Gulf of Finland. The maximum proportion of M. rubrum in the photosynthetic plankton community was estimated up to 88% in May and up to 91% in June. We relate the observed post-spring bloom decrease of phosphate concentrations in the surface layer to the dominance and growth of M. rubrum. We suggest that this link can be explained by the vertical migration behaviour of M. rubrum and phosphate utilization in the surface layer coupled with inorganic nitrogen assimilation in the sub-surface layer. Thus, the dynamics of M. rubrum could strongly influence the amount of post-spring bloom excess PO43- in the euphotic layer and the depth of nitracline in the Gulf of Finland.